An international comparison of HIV prevalence and incidence in blood donors and general population: a BEST Collaborative study. Issue 10 (9th April 2021) - Germain, Marc; Grégoire, Yves; Custer, Brian S.; Goldman, Mindy; Bravo, Marjorie; Kamel, Hany; Davison, Katy; Field, Stephen; van den Hurk, Katja; van de Laar, Thijs J. W.; Irving, David O.; Jones, Ann; et al.
Abstract : Background and Objectives: Efficiency in mitigating HIV transmission risk by transfusion may vary internationally. We compared HIV prevalence and incidence in blood donors across different jurisdictions in relation to those rates in the general population and differences in deferral practices. Materials and Methods: Data from 2007 to 2016 were collected in Australia, Brazil (São Paulo), Canada, England, France, Italy, Ireland, Japan, the Netherlands, New Zealand, Norway, Spain (Basque Country), USA (Vitalant) and Wales. For each country/region, the number of HIV antibody‐positive donations and nucleic acid testing (NAT)‐only‐positive donations was broken down according to first‐time or repeat donor status, along with the relevant denominators. Results: There is a modest correlation between HIV prevalence among first‐time donors and HIV prevalence in the general population. However, rates of HIV‐positive donations in repeat donors, a proxy for incidence, do not correlate with incidence rates in the general population. Rates in donors from Italy and Basque Country, where deferral criteria for men having sex with men are less stringent, are higher compared with most other jurisdictions. Rates of NAT‐only‐positive donations are extremely low and do not differ significantly after adjustment for multiple comparisons. Conclusion: Donor HIV rates are only weakly associated with those observed in the general population. Countries with less stringent deferral criteria have higher HIV rates in their donor population, but the rates remain very low.